The Role of Trust, Literacy, Effectiveness, and Convenience in Online Zakat Payment (Prodi Ekonomi Syariah Pascasarjana IAIN Kudus, 2025)
This study examines the factors that influence individuals' decisions to utilize the National Zakat Agency (BAZNAS) website for zakat (mandatory religious tax) payments in the Jabodetabek area of Indonesia, focusing on the roles of trust, zakat literacy, effectiveness, and convenience. It addresses a critical research gap concerning the under-explored synergistic interplay of psychosocial (trust and literacy) and technical (effectiveness/ perceived usefulness, convenience/ perceived ease of use) factors in shaping digital zakat adoption within Indonesia's mature digital ecosystem. While existing literature often isolates these variables, this paper offers originality by empirically testing their simultaneous correlations using advanced Structural Equation Modeling (SEM), contextualized for BAZNAS’s evolving platforms. A descriptive quantitative design was employed, with data collected through structured questionnaires distributed to a purposive sample of 100 Muslim respondents who had used the BAZNAS website. The findings reveal that effectiveness and convenience significantly impact payment decisions, whereas trust and zakat literacy do not have a significant impact. Respondents prioritize the perceived usefulness of BAZNAS’s programs, valuing their sustainable impact beyond financial aid, as well as the perceived ease of use provided by the website’s user friendly features, such as clear payment instructions. The non-significance of trust and literacy suggests that, within this mature digital context, they function as foundational prerequisites rather than dynamic influences, challenging initial assumptions. This study contributes to the digital zakat adoption literature by integrating behavioral and technological perspectives, extending the Technology Acceptance Model (TAM), and providing practical guidance for BAZNAS to enhance digital strategies by emphasizing program effectiveness and platform usability.